Pengembangan Sistem E-Surat Perintah Penghentian Penyidikan Polrestabes Palembang Berbasis Web Dengan Metode RAD - Fauzan Azimah; Megawaty (STMIK Budi Darma, 2023)
So far, the processing of SP3 data at Polrestabes Palembang is done manually, namely administrative staff officers write in the SP3 ledger and then type on a computer with Microsoft Office Word, so problems arise, namely administrative staff complain because the process takes two times which takes a long time to write and input. SP3 data. Another problem arises when searching for SP3 data based on letter number takes quite a long time so it is not effective and efficient. During the apprenticeship program at Polrestabes Palembang, an SP3 system was made, but there were still deficiencies, namely administrative staff recapitulating data based on case categories within a month, still counting manually, therefore a development was made that would make it easier for administrative staff to automatically recap data. With the development of this feature will be more effective and efficient. The purpose of this research is to make the development of an investigation termination warrant system. The benefit of this research is to simplify and speed up the work of administrative staff in inputting and searching for SP3 data. The system development method in this study uses the RAD method. The stages of this method are Requirement Planning, RAD Design Workshop, Implementation, Testing. The results of this study are that administrative staff can input SP3 data anytime and anywhere because it is web-based